Wanneer die beelde uit die oog geneem word – teks en beeld: "n Teologiese probleem - Kloppers, Wilhelm C. (HTS teologiese studies, 2003)
When the images are taken out of sight – text and image: A theological issueThe over-emphasis of the Lutheran theology according to which the "ears alone" would be appropriate, as well as the Barthian theology of "the word alone", led to a negative evaluation of images and the visual aspects of communication. In this article it is argued that texts and images are sides of the same coin which both contribute to under-standing and which therefore communicate the faith in ways that are different, yet very similar. When text and image are separated, it leads to deficient imagination and communication. It is shown that theology cannot escape the forming of images and communication through images. Theologians therefore need profound training in the understanding of images and in creative communication through images and imagination – theologians need Bild-ung.